All-pay contests with constraints - Ivan Pastine; Tuvana Pastine (University College Dublin, UCD School of Economics, 2012)
This paper provides simple closed form formulae for players' expected payoffs in a broad class of all-pay contests where players may have constraints on their actions.
Keywords: 330